SYMPOSIUM EDITOR'S INTRODUCTION - HENDERSON, ALEXANDER C. (Journal of health and human services administration, 2017)
A number of new health care programs are extending traditional hospital, private practice, or clinic-based health care into the home. These programs, currently operating under the labels of "community paramedicine" (CP), "mobile integrated health" (MIH), or "extended care practitioners" (ECP) often employ registered nurses, paramedics, emergency medical technicians, or other frontline clinicians to provide health care in a home-based setting, focusing on both acute care and management of diseases (Kizer, Shore, & Moulin, 2013; Patterson & Skillman, 2013).